-4+5n=6

Simple and best practice solution for -4+5n=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4+5n=6 equation:


Simplifying
-4 + 5n = 6

Solving
-4 + 5n = 6

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 5n = 6 + 4

Combine like terms: -4 + 4 = 0
0 + 5n = 6 + 4
5n = 6 + 4

Combine like terms: 6 + 4 = 10
5n = 10

Divide each side by '5'.
n = 2

Simplifying
n = 2

See similar equations:

| 3x-46x+1=0 | | n+17.9=18.3 | | 15d-8d+13=55 | | x-10=7.2 | | (x^5)-i=0 | | 2x-1x+3=0 | | 12-48n^2= | | 0.87=(0.13*2^x)/x! | | x/7-1=0 | | 3x^2-30x=69 | | -3x-4(-6x-10)=187 | | 7x^2y+14xy=7xy(x+2) | | X^2-10x+75=98 | | abs-x^2-3x+5abs=-4 | | 2+14n=17+10n+5n | | -6x+6(4x-12)=-198 | | M/-5-3 | | I-x^2-3x+5I=-4 | | 3k=9+2k | | 14=4(v+2)-2v | | 45v=4 | | 5x/4=15/4 | | -72+(30)= | | -14=8(x-4)-2x | | -50=-10(4+y) | | (p-2s)/2 | | 3x^2+10x+25=17 | | -17s-17=-19s+17 | | -6(1+q)=-72 | | 2/3z=-8 | | 60=7x+5y | | 11/12x7/8 |

Equations solver categories